Sustainable lignin‐based polyols as promising thermal energy storage materials. Issue 46 (7th July 2021) - Perez‐Arce, Jonatan; Serrano, Angel; Dauvergne, Jean‐Luc; Centeno‐Pedrazo, Ander; Prieto‐Fernandez, Soraya; Palomo Del Barrio, Elena; Garcia‐Suarez, Eduardo J.
Abstract: Six lignin‐based polyols (LBPs) have been prepared by cationic ring opening polymerization of an oxirane in the presence of an organosolv lignin in tetrahydrofuran (THF) as reaction media and co‐monomer. The prepared LBPs have been characterized and tested for the first time as phase change materials (PCMs) for thermal energy storage (TES) at low temperature. It was found a strong influence of the LBPs composition on their performance to storage thermal energy. Thus, LBPs with higher THF wt% content and lower oxirane/THF mass ratio exhibit the highest latent heats. Furthermore, a clear inversely proportional trend between the oxirane/THF mass ratio and the melting temperatures of the prepared LBPs was noticed. Among the prepared LBPs, the highest obtained latent heat was 53.7 J/g demonstrating the potential application of lignin as feedstock for PCMs preparation. To the best of our knowledge, this is the first time that a biomass derived PCM based on lignin has been studied and considered for TES applications at low temperature. LBPs show energetic solid–liquid transitions that point out their promising potential as bio‐PCMs. This work paves the way to introduce new bio‐based PCMs from lignin in TES systems, for example, in a more sustainable construction sector. Abstract : Lignin has been upgraded to thermal energy storage material (LBP) and the highest obtained latent heat was 53.7 J/g demonstrating the potential application of lignin as feedstock for PCMs preparation. To the best of our knowledge, this is the first time that a biomass derived PCM based on lignin has been studied and considered for TES applications at low temperature. This work paves the way to introduce new bio‐based PCMs from lignin in TES systems.